Upcoming Deliberative Waves and the Needs to Redesign Indonesian People’s Consultative Assembly - ., Martuli; Handayani, I Gusti Ayu Ketut Rachmi; Riwanto , Agus (Journal of Ecohumanism, 2024)
This study shows the urgency of strengthening the function of deliberative institutions that should be able to guard the interests of the community and the constitutionality of the law. The amendment to the 1945 Constitution shows how legal issues began to emerge when the People’s Consultative Assembly was no longer authorized to determine the General Outline of State Policy and how the Constitutional Court failed to be the sole guardian of the Constitutionality of National Policy. This study continues the research that discusses how democracy affects the performance of public institutions. The study results show that changes in the characteristics of the People’s Consultative Assembly have changed the institution’s function so that the legislative process to determine the entire direction of policy comes purely from officials elected through the general election system. Institutionalization to formulate alternative representation models and strengthen institutions for deliberative institutions is needed to improve the performance of the Indonesian system, society, and democracy. This study offers a redesigned scheme for MPR membership by restoring the representation of community groups to strengthen democracy and ensure proportionality of community representation. The results of this study are an essential consideration for maintaining the suitability of democratic values ​​with the goals of the Indonesian nation.